La representación legal de las sociedades comerciales en Colombia y el problema de principal y agente. Soluciones - Delvasto P., Carlos Andrés (2023)
This article describes the principal-agent problem within firms. The author outlines diverse solutions, emphasizing the agentís incentives created by Law 222 of 1995. The article is divided in six parts. The author begins by explaining the convenience, from a legal and economic perspective, of having organizations and economic agents. Second, the article describes the types of corporations found in Colombia, paying particular attention to two points: a) legal personality, and b) the ownerís responsibility. Third, the author describes the principal-agent problem, and also, fourth, the way in which it appeours in economic organizations. Fifth, this paper addresses possible solutions laid down by Law 222 of 1995, and, finally, it presents the authorísconclusions.